PENCEGAHAN DAN PENANGGULANGGAN COVID-19 DI DESA GENTAN KECAMATAN BAKI KABUPATEN SUKOHARJO - Siti Maryam; Sri Hartono; Eny Kustiyah; Yusnia, Novi, Anik, Yuliana, Titis, Asiah, Yuli, Riesky (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2021)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. This disease due to viral infection is called COVID-19. Corona virus can cause disturbances in the respiratory system, acute pneumonia, to death. Based on the Circular of the Secretary General of the Indonesian Ministry of Health No.PK. 02.01 / B.VI / 839/2020 dated 05 March 2020 concerning the Appeal for Prevention of COVID-19 Transmission, namely the Government instructs everyone to obey health protocols such as wearing masks, washing hands and maintaining distance or avoiding crowds and implementing a clean lifestyle such as always wearing handsanitizer and maintain a healthy diet by eating lots of vegetables and fruit and avoiding eating raw meat. For this reason, the implementation of KKN (Real Work Lecture) of the Islamic University of Surakarta in 2020 in Gentan Village, Baki District, Sukoharjo Regency with a thematic theme adapting to the current situation, this program also helps the government to break the chain of Covid-9 spread, by carrying out several programs such as Socialization of Covid-19 Prevention, giving handsanitizers and masks, tutoring for Kindergarten-SMP level children, social services, spraying disinfectant fluids, distributing vitamins, distributing brochures to prevent the spread of covid-19 Keywords: KKN UNIBA Surakarta, Gentan Village, Prevention of Covid-19 transmission, Health Protocol